ACCOUNTING AND CODE REGULATION. - Taggart, H. F.; Castenholz, W. B. (The Accounting Review, 1935)
Abstract Accounting data and procedures impinge upon the National Reform Association (N.R.A.) codes and their administration at a number of points. There is for example, the matter of keeping the books and auditing the accounts of Code Authorities. These bodies, whose precise legal status is still a matter of considerable uncertainty, are permitted to collect in a compulsory manner funds from the members of industries under their guidance, and to spend those funds on the basis of budgets approved by the N.R.A. officials in Washington. Accounting data have been extremely useful in the making and amending of codes. The best example of such aid is the ascertainment of the effect of proposed wage and hour provisions on costs. The N.R.A. appears to the author as a challenge to industrial accounting practitioners to bring into play talents which will begin to act because of a recognition that all business transactions are in reality cost matters finding expression not only in the processes of making goods and marketing goods but also in the processes of capital investment and economic readjustments.